Transformative Learning Theory: Suatu Proposal untuk Melengkapi Ide Liberal Arts Arthur Holmes di dalam Aplikasinya bagi Pendidikan Tinggi Kristen [Transformative Learning Theory: A Proposal to Complement Arthur Holmes’ Idea of Liberal Arts in Its Application for Higher Christian Education] - Yanti - Yanti (Universitas Pelita Harapan, 2020)
This research is generated from the longing to re-actualize Christian higher education significant impact. Intentionally, this research is addressed to complement the idea of Liberal Arts by Arthur F. Holmes, as an effort to re-actualize an integrated Christian higher education. Therefore, this research is mainly focused on Holmes thoughts on Liberal Arts and his ideas on Christian higher education, continued by analysing on how his purpose can be supported by the implementation principles of transformative learning theory. Transformative learning theory will be discussed specifically before being compared to Liberal Arts as to figure out the potential formula for collaboration. This research is not intended to solve all existing problems of Liberal Arts and transformative learning theory, as well is not resulted in a curriculum design and its application. This research is intended to explain theoretical – philosophical as the beginning of an idea of the potential collaboration between Liberal Arts and transformative learning theory. This paper will explore the possibility of applicative integration between Liberal Arts and transformative learning theory. The finding will be obtained by exploring the role of transformative learning theory for Liberal Arts in fulfilling the profile of an educated person, in accordance with the ideals of Holmes through Liberal Arts education.